#TITLE_ALTERNATIVE# - MUKTI TRI HARJANTI (NIM 13411034), CITRA
Emergency Department is a department in a hospital that provides emergency services dedicated for emergency patients. Emergency patients who often require immediate treatment should be cared and monitored by the Emergency Unit, so the hospital management should make sure that quick and accurate services level is provided to them. Furthermore, one of the most common paramater which is usually used to measure the speed of emergency medical service in the Emergency Department is response time. Response time is the time between the moment of patient arrival at the Emergency Department until the patient is properly handled by the Emergency Unit Doctor. Based on Keputusan Menteri Kesehatan Republik Indonesia Nomor 856 Tahun 2009 by Indonesian Health Ministry, response time itself shouldn't takes longer than five minutes. The main purpose of this research is to determine the most valuable option of resources which is needed in RSAU dr. M. Salamun Emergency Department to accelerate emergency service speed in order to cope with national emergency service time standard by conducting experiments and simulation model analysis. Discrete Event Simulation and Area Simulation Software is used to perform and to visualise the model. At the end of the research, the average response time in RSAU dr. M. Salamun Emergency Department can be lowered from 6.05 minutes to 4.33 minutes, and the maximum response time can also be lowered from 95.29 minutes to 7.12 minutes by adding 3 addition beds, 4 nurses per shift and 2 doctors per shift.